TRANSFORMATION OF TRADISIONAL TREATMENT SYSTEM IN MAKASSAR (Jurnal Suara Kesehatan, 2014)
Transformation of traditional treatment systems in Makassar is a system of medicine that is undertaken by the society in addition to medical treatment. The system is rapidly used community. This research aims at examining the process of transformation of society to use medical drugs in addition to traditional medicine in a cure, treatment and prevention of some types of disease. The research was qualitative research. The data were obtained through observation, interview, and documentation. The data were then analysed by reduction of the data, presentation of data, conclusion, and the theory of symbolic interaction. The results showed that the transformation of the traditional treatment system in healing and treatment of society in Makassar is performed with the belief that God Almighty (Allah SWT) creates the medicine for every disease that appears. In addition, the process of healing and treatment of disease suffered by society in Makassar is performed by using herbal medicine such as consuming foods that contain nutrition. In order to avoid disease, body care is urgently needed by every human beings.